Time-restricted ketogenic diet in amyotrophic lateral sclerosis: a case study - Phillips, Matthew C. L.; Johnston, Samuel E.; Simpson, Pat; Chang, David K.; Mather, Danielle; Dick, Rognvald J. (Frontiers in Neurology, 2024)
Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disorder. The most devastating variant is bulbar-onset ALS, which portends a median survival of 24 months from the onset of symptoms. Abundant evidence indicates that neuron metabolism and mitochondrial function are impaired in ALS. Metabolic strategies, particularly fasting and ketogenic diet protocols, alter neuron metabolism and mitochondria function in a manner that may mitigate the symptoms of this disorder. We report the case of a 64-year-old man with a 21-month history of progressive, deteriorating bulbar-onset ALS, with an associated pseudobulbar affect, who implemented a time-restricted ketogenic diet (TRKD) for 18 months. During this time, he improved in ALS-related function (7% improvement from baseline), forced expiratory volume (17% improvement), forced vital capacity (13% improvement), depression (normalized), stress levels (normalized), and quality of life (19% improvement), particularly fatigue (23% improvement). His swallowing impairment and neurocognitive status remained stable. Declines were measured in physical function, maximal inspiratory pressure, and maximal expiratory pressure. Weight loss was attenuated and no significant adverse effects occurred. This case study represents the first documented occurrence of a patient with ALS managed with either a fasting or ketogenic diet protocol, co-administered as a TRKD. We measured improved or stabilized ALS-related function, forced expiratory volume, forced vital capacity, swallowing, neurocognitive status, mood, and quality of life. Measurable declines were restricted to physical function, maximal inspiratory pressure, and maximal expiratory pressure. Now over 45 months since symptom onset, our patient remains functionally independent and dedicated to his TRKD.